#### Answer

$12$

#### Work Step by Step

$(\frac{f}{g})(x)=\frac{f(x)}{g(x)}$
$f(-4)=(-4)^2-3(-4)+8=16+12+8=36$
$g(-4)=-2(-4)-5=8-5=3$
$(\frac{f}{g})(-4)=\frac{f(-4)}{g(-4)}=\frac{36}{3}=12$

Chegg costs money, GradeSaver solutions are free!

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$12$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.